The Effectiveness of the Real Food Consumption Education Programme on Nutritional Knowledge among the Youth Red Cross Community - Silvia Dewi Styaningrum; Endri Yuliati; Siska Puspita Sari; Fera Noviartika; Kuntari Astriana (JURNAL KESMAS DAN GIZI (JKG), 2026)
Adolescents in Indonesia face complex nutritional challenges, primarily due to high consumption of ultra-processed foods (UPFs) and excessive intake of sugar, salt, and fat (SSF), which contribute to an increased risk of non-communicable diseases (NCDs). Nutrition education in schools is a strategic approach to fostering healthy eating behaviours. This study aims to measure the effectiveness of nutrition education on the consumption of real food using a lecture and question-and-answer method within the Red Cross Youth (PMR) community. This study employs a quantitative approach, using a quasi-experimental design (one-group pretest-posttest design). A total of 82 PMR student members participated in completing the pre-test and post-test questionnaires. The educational material covered the definition and examples of real food, the health risks associated with ultra-processed foods (UPFs), restrictions on the consumption of sugar, salt, and fat (SSF), and how to read processed food labels. The instrument used to measure knowledge was a validated 15-item multiple-choice questionnaire completed via a Google Form link. Analysis using the Wilcoxon signed-rank test revealed a statistically significant difference in median pretest and posttest scores (p = 0.000). There was an increase in the median knowledge score from 83.33 to 100. A total of 53.66% of students improved their knowledge scores following the education. Nutrition education on real food, delivered through a lecture and question-and-answer method, proved effective in improving the nutritional knowledge of PMR members. PMR members are expected to act as peer educators by sharing knowledge and promoting healthy eating behaviours to their peers within the school community.